"Planting the Seeds": The Influence of the Council on Education Policy and Practice. Issue 13 (December 2015) - Bertrand, Melanie; Ford, Arlene J.
This chapter explores the influence of a youth participatory action research (YPAR) group, viewing the group's efforts as challenges to manifestations of racial inequality in education, such as the inequitable distribution of educational resources. The authors examine how individuals in positions of relative power—teachers, school administrators, and public officials— respond to the group's advocacy efforts. The analysis illustrates the complexity of the group's influence: Some individuals report that the Council sparks meaningful changes, while others have negative reactions. Overall, the chapter sheds light on the ways that YPAR can encourage change in education by incorporating the voices of Black and Latina/o youth into educational policy and practice. "What really stuck with me was this idea of traditional versus organic forms of leadership… and that it's my responsibility to help my students develop as leaders." – Ms. Bauman 1